Understanding a videogame home intervention for children with hemiplegia: a mixed methods multi-case study - Chan-Víquez, Daniela; Khan, Ajmal; Munce, Sarah; Fehlings, Darcy; Wright, F. Virginia; Biddiss, Elaine (Frontiers in Medical Technology, 2023)
Introduction Access to rehabilitation therapies is a salient and growing issue for children with cerebral palsy (CP) and their families, motivating interest in home-based interventions. Bootle Blast is a low-cost, movement-tracking videogame that can be used at home to encourage upper limb (UL) functional exercise tailored to each child's abilities and therapy goals. The study objectives were to: 1) Establish the extent to which children achieve their self-directed play-time goal over a 12-week intervention, 2) Measure changes in UL motor outcomes, and 3) Explore participants' experiences of using Bootle Blast at home. Methods Mixed methods case series study of four children with hemiplegic cerebral palsy (HCP), each with a participating parent. Participants played Bootle Blast at home for 12 weeks. Study assessments occurred at baseline, post-intervention and four week follow up. A post-intervention interview explored participants' experiences. Game-logs provided play time and progress data. Results Three of four participants (8-13 yrs., Manual Ability Classification Level I-II) completed the intervention. One dropped out at week 6. Play-time goals were achieved in most weeks, with two of four children surpassing their overall intervention goals. Outcomes varied across the three participants, however consistent improvements were observed on the Canadian Occupational Performance Measure and the Box and Blocks Test. Inductive analysis generated four main themes: 1) Intrinsic motivators fostered play engagement, 2) Virtual play for real-world gains, 3) Therapy on demand (at home), and 4) Shifting the onus from the parent to the game. Integration of qualitative and quantitative data was important for interpreting play patterns/usage and clinical outcomes. Discussion This mixed methods study describes a novel videogaming intervention designed for home-rehabilitation for children with HCP and provides preliminary evidence to guide future study design and research. Clinical Trial Registration [https://clinicaltrials.gov/ct2/show/NCT04009031?recrs=h&cond=Cerebral+Palsy&cntry=CA&city=Toronto&draw=2&rank=1], identifier [NCT04009031].